2023
DOI: 10.3389/fpsyg.2023.1134052
|View full text |Cite
|
Sign up to set email alerts
|

Contextual considerations for deception production and detection in forensic interviews

Abstract: Most deception scholars agree that deception production and deception detection effects often display mixed results across settings. For example, some liars use more emotion than truth-tellers when discussing fake opinions on abortion, but not when communicating fake distress. Similarly, verbal and nonverbal cues are often inconsistent predictors to assist in deception detection, leading to mixed accuracies and detection rates. Why are lie production and detection effects typically inconsistent? In this piece,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…However, the Resume deceivers had to be more proactive in order to promote the less favored candidates. Clearly, the context shapes verbal content and style and argues for conducting experiments in the context of interest rather than “borrowing” conclusions from other investigations (see Markowitz et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the Resume deceivers had to be more proactive in order to promote the less favored candidates. Clearly, the context shapes verbal content and style and argues for conducting experiments in the context of interest rather than “borrowing” conclusions from other investigations (see Markowitz et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between political ideology and deception is more mixed and lie‐type dependent, however. That is, Markowitz et al (2023) suggested people who are more conservative tend to self‐report more big and serious lies (Study 2), but the relationship between conservatism and self‐reported white lying was not statistically significant. Altogether, prior evidence indicates that demographics often matter in predicting deception rates and deception dynamics, which motivated their evaluation in this work.…”
Section: Deconstructing Deceptionmentioning
confidence: 91%
“…tive of embedded deceiving or truth-telling, or if a person's embedded deceiving (or truth-telling) rate in one setting is associated with their embedded deceiving (or truth-telling) rate in another setting (or, as others likeSerota et al, 2022 question, if one's prolific lying status is consistent over time). The contextual similarities and constraints of a deception setting are also worth investigating as they relate to embedded deceiving(Markowitz et al, 2023;Markowitz & Hancock, 2019), since prior work suggests that elements of the context (e.g., psychological dynamics, pragmatic goals, genre conventions, dispositional factors, situational factors, interpersonal factors) can shape how deception affects language. Altogether, while this current work has pushed the concept of embeddedness forward in new ways, future research would benefit from taking this idea more seriously in the deception literature to understand its social, psychological, and cultural antecedents and consequences.Finally, when participants indicated their embedded deceptions, they did not rate the severity of such messages (e.g., as a little white lie or a big lie) beyond a simple Likert-type scale rating of deceptiveness.…”
mentioning
confidence: 99%
“…It may be helpful to examine if one's tendency to behave deceptively on one-off tasks is predictive of embedded lying or truthtelling, or if a person's embedded lying (or truth-telling) rate in one setting is associated with their embedded lying (or truth-telling) rate in another setting (or, as others like Serota et al 2022 question, if one's prolific lying status is consistent over time). The contextual similarities and constraints of a deception setting are also worth investigating as they relate to embedded lying (Markowitz et al, 2023;Markowitz & Hancock, 2019), since prior work suggests that elements of the context (e.g., psychological dynamics, pragmatic goals, genre conventions, dispositional factors, situational factors, interpersonal factors) can shape how deception affects language.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%